Cardiac structure and function in elite female athletes: A systematic review and meta-analysis - Bryde, R.; Applewhite, A. I.; Abu Dabrh, A. M.; Taylor, B. J.; Heckman, M. G.; Filmalter, S. E.; Pujalte, G.; Rojas, C.; Heckman, A. J.; Brigham, T. J.; Prokop, L. J.; Shapiro, B. P. (Physiological Reports, 2021)
We conducted a meta-analysis to synthesize the best available evidence comparing cardiac biventricular structure and function using cardiac magnetic resonance imaging (CMR) and transthoracic echocardiography (TTE) in elite female athletes and healthy controls (HC). Chronic exposure to exercise may induce cardiac chamber enlargement as a means to augment stroke volume, a condition known as the "athlete's heart." These changes have not been clearly characterized in female athletes. Multiple databases were searched from inception to June 18, 2019. Outcomes of interest included left ventricular (LV) and right ventricular (RV) dimensional, volumetric, mass, and functional assessments in female athletes. Most values were indexed to body surface area. The final search yielded 22 studies, including 1000 female athletes from endurance, strength, and mixed athletic disciplines. CMR-derived LV end-diastolic volume (LVEDV) and RV end-diastolic volume (RVEDV) were greater in endurance athletes (EA) versus HC (17.0% and 18.5%, respectively; both p < 0.001). Similarly, TTE-derived LVEDV and RVEDV were greater in EA versus HC (16.8% and 28.0%, respectively; both p < 0.001). Both LVEF and RVEF were lower in EA versus HC, with the most pronounced difference observed in RVEF via TTE (9%) (p < 0.001). LV stroke volume was greater in EA versus HC via both CMR (18.5%) and TTE (13.2%) (both p < 0.05). Few studies reported data for the mixed athlete (MA) population and even fewer studies reported data for strength athletes (SA), therefore a limited analysis was performed on MA and no analysis was performed on SA. This evidence-synthesis review demonstrates the RV may be more susceptible to ventricular enlargement. General changes in LV and RV structure and function in female EA mirrored changes observed in male counterparts. Further studies are needed to determine if potential adverse outcomes occur secondary to these changes.